Analysis of Students' Mastery of Basic Physics Concepts in Lectures Using E-Books - Hikmawati, Hikmawati; Ayub, Syahrial (Balai Publikasi Indonesia, 2023)
The use of teaching materials has many benefits for students, one of which is to make it easier for students to find information and assist in mastering concepts. This pre-experimental study aims to describe students' mastery of Basic Physics concepts in lectures using e-books. The subjects of this study consisted of all students taking Basic Physics courses at the Biology Education Study Program, University of Mataram, with a total of 27 students. The research was conducted in 7 meetings, starting from October 24 2022 to December 5 2022. The concepts studied consisted of: Static Fluid, Dynamic Fluid, Vibration and Waves, Temperature and Heat. Student concept mastery data was obtained from giving essay tests at the 8th meeting. The level of mastery of the concept is divided into 8 grades namely A, B+, B, C+, C, D+, D, E. Students are declared to have passed if they get grade C, with levels of mastery of concepts ranging from 65 to less than 70. The results showed that the grades the lowest is 66.2 (grade C), while the highest is 91.5 (grade A). The average value of concept mastery is 77.8 (grade B). Thus, it can be concluded that the percentage of students' concept mastery who obtain a pass grade of 100%. The use of e-books can be an alternative teaching material that can be used by lecturers and students in an all-digital era. E-book users can access anytime and anywhere